2014
DOI: 10.1093/mp/ssu063
|View full text |Cite
|
Sign up to set email alerts
|

A DTX/MATE-Type Transporter Facilitates Abscisic Acid Efflux and Modulates ABA Sensitivity and Drought Tolerance in Arabidopsis

Abstract: Abscisic acid (ABA) regulates numerous physiological and developmental processes in plants. Recent studies identify intracellular ABA receptors, implicating the transport of ABA across cell membranes as crucial for ABA sensing and response. Here, we report that a DTX/Multidrug and Toxic Compound Extrusion (MATE) family member in Arabidopsis thaliana, AtDTX50, functions as an ABA efflux transporter. When expressed heterologously in both an Escherichia coli strain and Xenopus oocyte cells, AtDTX50 was found to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
209
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(220 citation statements)
references
References 35 publications
3
209
0
Order By: Relevance
“…3 D and E). The DTX33 and DTX35 transporters were not significantly permeable to organic acids, including citric acid and malate, in contrast to the MATE transporters described previously, including those mediating aluminum tolerance (18)(19)(20)(21)(22)29). It is noteworthy that both DTX members are slightly permeable to nitrate, which can be an abundant inorganic anion in plant cells under certain soil conditions.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…3 D and E). The DTX33 and DTX35 transporters were not significantly permeable to organic acids, including citric acid and malate, in contrast to the MATE transporters described previously, including those mediating aluminum tolerance (18)(19)(20)(21)(22)29). It is noteworthy that both DTX members are slightly permeable to nitrate, which can be an abundant inorganic anion in plant cells under certain soil conditions.…”
Section: Resultsmentioning
confidence: 57%
“…We then measured the transport activity of isolated vacuoles from fluorescence-labeled cells by patch-clamp procedure (28). Several studies indicated that DTX/ MATE-type proteins transport organic acids, such as citric acid (18)(19)(20)(21)(22)29). We examined the possibility that DTX33 and DTX35 may function as anion transporters, like those reported earlier.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, recent studies have identified MATE transporters that are localized to plasma membrane, chloroplast, endomembrane systems (Li et al, 2002;Burko et al, 2011;Seo et al, 2012;Serrano et al, 2013;Li et al, 2014;Zhang et al, 2014). To determine to which membrane system the BIGE1 MATE transporter is localized, maize BIGE1 was fused with GFP at the C terminus and expressed under the control of the 35S promoter in stably transformed Arabidopsis.…”
Section: Subcellular Localization Of the Bige1 Mate Transportermentioning
confidence: 99%
“…These transporters are involved in ABA efflux and influx with tissue-specific expression. Very recently, an Arabidopsis DTX/MATE family member, DTX50, has been shown to function as a mediator of ABA efflux (9).…”
mentioning
confidence: 99%